Point-of-sale marketing of heated tobacco products in Israel: cause for concern - Bonnie Halpern-Felsher (Israel Journal of Health Policy Research, 2019)
Abstract Understanding how PMI markets IQOS at the point-of-sale in Israel is critical to determining whether marketing practices adhere to regulations and appeal to groups most at risk at initiating new tobacco products, such as adolescents. An article by Bar-Zev, Levine, Rubinstein, Khateb, and Berg (2019) examined the marketing of IQOS in retail stores in Israel. They found that while no free samples or promotions were provided at the point-of-sale, IQOS and their related HEETS (HeatSticks) were placed near youth-oriented merchandise and in prominent locations easily seen by youth. Further, package colors were used to indicate tobacco flavorings and strength, and retailers described the IQOS products as being less harmful, a cessation device, and not producing smoke. These findings are concerning given numerous studies linking marketing of novel tobacco products, product misperceptions, and subsequent tobacco use. Studies are needed to ensure that the marketing of IQOS, including the use of package colors, product placement at point-of-sales, and other product characteristics are significantly reducing harm and risk of tobacco-related disease to IQOS users, and that the health of the population as a whole, including those not using IQOS or other tobacco products, will not be harmed. Until such evidence is available, caution is warranted and regulations needed in the marketing of these novel products.